Analysis of the healthcare waste management status in Tehran hospitals - Malekahmadi, Fariba (J Environ Health Sci Eng, 2014)
BACKGROUND: Considering the importance of healthcare waste management, following the ratification of the Waste Management law in 2005 and the subsequent approval of its executive bylaw in 2006 and finally the healthcare waste management criteria passing by the parliament in 2008, a review on the status of healthcare waste management is needed to implement the mentioned law properly. FINDINGS: In this retrospective study during six months period all public hospitals in Iran’s capital city, Tehran, were selected to conduct the survey. Data collected through an expert-standardized questionnaire was analyzed by using SPSS software. The results of the current status of healthcare waste management in Tehran hospitals showed 5.6% of hospitals were ranked excellent, 50.7% good, 26.4% medium, and the 13.9% of hospitals were ranked weak and 3.5% ranked very poor. CONCLUSIONS: The findings showed that appropriate technologies should be used to have better disposal stage. As the ratified criteria were not fully observed by all the selected hospitals, training courses and comprehensive program conducting by each hospital could be enjoyed as practical tools to implement the all stages of healthcare waste management properly.